Incidental occurrence of neutropenia in children hospitalised for COVID-19 - Francesco Folino; Camilla Menis; Giada Maria Di Pietro; Raffaella Pinzani; Paola Marchisio; Samantha Bosis (BMC, 2022)
Abstract Background Investigations on haematological alterations in paediatric COVID-19 have been focused mostly on lymphocytes and clotting profiles. Neutropenia has been occasionally reported and its course and impact on the disease have not been elucidated. The aim of this study was to describe the epidemiology, course, and impact of neutropenia in children with COVID-19 hospitalised in a tertiary care referral paediatric ward. Methods A single-centre retrospective study was conducted. Hospitalised children between 1 month and 18 years with confirmed COVID-19 and neutropenia were included and compared to non neutropenic patients. Complete blood picture with differential blood count, serum biochemistry, clotting profiles were performed; clinical data, length of hospitalisation, and prescription of drugs were collected. Results Twelve out of 95 patients (12.63%) with documented SARS-CoV-2 infection were neutropenic and met the inclusion criteria. The mean age was 161 days (range 38-490 days). The mean duration of symptoms in neutropenic children was 3.82 days, while the mean length of hospitalisation was 7.67 days. These findings were not significantly different in the two study groups. All patients had mild clinical manifestations and were discharged without sequelae. Conclusions We provided the first comprehensive study on neutropenia in mild paediatric COVID-19 infection. Our findings show that the main features of this haematological disorder in COVID-19 are analogous to the well-known transient benign neutropenia associated with other common viral infections. In our setting, neutropenia does not emerge as a potential negative prognostic factor in paediatric COVID-19.